The administration of social and solidarity economy companies - Acosta Velarde, Rosa; Campaña, María Verónica; Flores Dávila, Jaime; Melendres Medina, Marcelo (mktDESCUBRE; Vol 1 No 1 (2020): InnovaEc 2019 Special Edition Congress, 2020)
The social economy and solidarity (ESS) is becoming a social economic order, although it is not new, it is gaining much prominence for some years. This system is being seen as a social good and an orientation to people, as well as an economic system, more democratic and an alternative to the capitalist systems of the world, which does not pursue the aims and profitability of traditional companies, but rather It is in charge of public welfare with all the members that have a company. However, concerns about scalability and integration with markets have become a need for a systematic evaluation of ESS companies. Therefore, this article is analyzed and ES companies are being successfully managed in terms of financial resources, accounting and human resources. The article examines successful initiatives and businesses of the ESS.